PENGARUH SISTEM PENGENDALIAN INTERN TERHADAP PEMBERIAN KREDIT GADAI PADA PT. PEGADAIAN (PERSERO) CABANG SUKABUMI - Fani Anggraeni (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2021)
This study aims to determine the effect of the Effectiveness of Internal Control System Pawn Lending at PT. Pegadaian (Persero) Branch Sukabumi. The variables used in this study of Internal Control System and Lending. The scale used is ordinal scale. Data were collected and then analyzed using validity and reliability test, test the classical assumption of normality, simple regression analysis, hypothesis testing using t test and coefficient of determination. Validity test results showed that all statements for the independent variables and the dependent variable is declared invalid. Reliability test results show that the instruments are independent and dependent variables is reliable. The result of the classical assumption of normality shows that the effect on the of internal control systems of credit pawn normal distribution. Results of testing the hypothesis (t-test) showed that the internal control systems significantly influence the of the provision of mortgage loans. Dah test results coefficient of determination of 77.9%. While the remaining 22.1% is influenced by other factors not examined.